Is Microendoscopic Discectomy Effective for Patients With Concomitant Lumbar Disc Herniation and Spondylolysis?. Issue 6 (September 2020) - Oshima, Yasushi; Inanami, Hirohiko; Iwai, Hiroki; Koga, Hisashi; Takano, Yuichi; Oshina, Masahito; Oka, Hiroyuki; Tanaka, Sakae
Study Design: A retrospective cohort study. Objective: Although it is controversial whether to choose only discectomy or fusion surgery in patients with disc herniation and spondylolysis, we expected that aggravation of the spondylolysis may be prevented if posterior supporting muscles can be well-preserved without extensive exploration. The purpose of this study was to investigate the influence of L5 spondylolysis on surgical outcomes following microendoscopic discectomy (MED) in patients with concomitant lumbar disc herniation and spondylolysis. Methods: We reviewed 811 patients who underwent MED for L4/5 or L5/S1 disc herniation. Patients with spondylolisthesis were excluded. We compared surgical outcomes of patients with and without L5 spondylolysis, whose age, sex, and surgical level were matched. Results: A total of 655 patients (80.7%) with complete data were considered eligible for the study. MED was performed at L4/5 and L5/S1 in 338 and 317 patients, respectively. A total of 20 patients (3.1%) had concomitant L5 spondylolysis and disc herniation at L4/5 (9 patients) or L5S1 (11 patients). As we compared each outcome of the 20 patients having L5 spondylolysis with 40 matched patients without L5 spondylosis, there were no significant differences in preoperative or postoperative outcomes between the 2 groups, and no patient with spondylolysis had undergone additional surgery during the mean follow-up period of 24 months. Conclusions: MED demonstrated good surgical results regardless of the presence or absence of spondylolysis. In patients with sciatica with concomitant disc herniation and spondylolysis, but without spondylolisthesis, fusion surgery may not be always necessary.